Materialidade e Base de Cálculo do IPTU - Lourenço, Vladimir Rossi (2007)
The constitutional concept of real estate for the purpose of Municipal Real Estate Tax (IPTU) fiscal incidence has always been controversial. Many professors defend an extensive interpretation, to cover not only the real estate itself, but also possession, dominium utile, the fee-farm, the right of surface, to give only three examples of types of rights in rem. Others do not accept this interpretation. After a simple review of Hans Kelsen and Niklas Luhmann s theories, there have been two new approaches of possible and different interpretations of the proposed theme. In Kelsen, a systematic interpretation led to a restrictive conception of the term, but even so, it permitted to come to the conclusion that the municipal legislator does have competence to enlarge the basis of tax incidence beyond the restricted definition of real estate. In the same way, based on the the systems theory, specially on the instruments extremely well handled by Luhmann, such as the structural coupling of various systems (communication) and even sub-systems, we have observed, a tendency to a admit a generalized conception, making it more comprehensive, in the same way, the term property, to cover, as well, other institutes defined as rights in rem by the Civil Code, as follows: possession, trust, fee-farm, dominium utile, and also, the right in rem of concession, for a determined term, by a public deed, the right of surface, regulated by the articles 1.369 to 1.377 of the Civil Code of 2002. The Municipal Real Estate Tax, (IPTU), that must be created by the Municipalities, and the Federal District, has as its own characteristics the tax progressiveness and selectiveness (increase of the percentage considering the higher and lower value, situation and use of the real estate in question, and also being progressive in time, (with increase and progressive percentage, as a sanction for the cases the owner does not follow the city master plan, forcing the real estate to fulfill its social function). Its taxation basis, whose criteria, must be established by law, can be altered by a lower law instrument